2019
DOI: 10.1155/2019/7213925
|View full text |Cite
|
Sign up to set email alerts
|

Changes in and Effects of Anxiety on English Test Performance in Chinese Postgraduate EFL Classrooms

Abstract: As an important affective factor in language learning, foreign language anxiety (FLA) has been extensively researched. Nevertheless, not many studies have targeted postgraduate students or been longitudinal to reveal the dynamic nature of FLA. Hence, the present quantitative study examined changes in and effects of FLA on postgraduate students’ performance over a 10-week period. A total of 324 postgraduate students from a prestigious university took a pretest and posttest, answered a set of questionnaires befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 53 publications
4
47
1
Order By: Relevance
“…Although some respondents reported that anxiety could be a motivator and urged them to do better, more respondents reported it to be a debilitator, as found in studies on SL/FL learners' FLA (Horwitz et al, 1986;Liu & Xiangming, 2019;Tobias, 1979;Tum, 2014). As confided by the respondents, anxiety led to a series of bad consequences, the worst of which were bad sleep, depression, lowered devotion to teaching, lowered motivation to work, becoming nervous, bad-temper, inability to focus on something, gray hair, procrastination, sickness, and lowered confidence, as found in similar studies (Cheung & Hui, 2011;Liu & Yan, 2020;Robinson & Clay, 2005;Yazici & Altun, 2013).…”
Section: Effects Of Anxietymentioning
confidence: 96%
See 1 more Smart Citation
“…Although some respondents reported that anxiety could be a motivator and urged them to do better, more respondents reported it to be a debilitator, as found in studies on SL/FL learners' FLA (Horwitz et al, 1986;Liu & Xiangming, 2019;Tobias, 1979;Tum, 2014). As confided by the respondents, anxiety led to a series of bad consequences, the worst of which were bad sleep, depression, lowered devotion to teaching, lowered motivation to work, becoming nervous, bad-temper, inability to focus on something, gray hair, procrastination, sickness, and lowered confidence, as found in similar studies (Cheung & Hui, 2011;Liu & Yan, 2020;Robinson & Clay, 2005;Yazici & Altun, 2013).…”
Section: Effects Of Anxietymentioning
confidence: 96%
“…Consequently, SL/FL learners may doubt their abilities, worry about their performance, and even have a mental block (Horwitz et al, 1986;Tobias, 1979). Studies using various methods like surveys, interviews, and diaries generally reveal a predominantly debilitating effect of FLA on SL/FL learning (Dewaele & Alfawzan, 2018;Horwitz, 2010;Horwitz et al, 1986;Liu & Xiangming, 2019). For example, Liu and Xiangming's (2019) longitudinal study on 324 Chinese postgraduate students found that FLA was highly related to the students' overall test performance as well as performance in English speaking, reading, listening, and writing, and that FLA was a powerful predictor of the latter, especially speaking test performance.…”
Section: Teaching Anxietymentioning
confidence: 99%
“…As reviewed below, Chinese learners of English at different educational levels often experience anxiety to varying degrees, which is largely because they have limited use of English in daily life (Liu, 2006(Liu, , 2016Lu and Liu, 2015;Liu and Xiangming, 2019). They may experience greater anxiety in online learning classrooms when they have even less use of English due to limited interaction and low motivation (Chen, 2010;O'Doherty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, although the current literature shows that foreign language anxiety, including FLCA and FLLA, is dynamic and multifaceted, studies on changes in different types of anxiety are still inadequate (Liu and Xiangming, 2019;Gregersen, 2020). Even fewer studies are available on the interaction of FLCA and FLLA though they have been shown to be independent constructs of foreign language anxiety (Horwitz et al, 1986;Elkhafaifi, 2005;Bekleyen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign language anxiety (FLA) has been found as a prevailing phenomenon among foreign language learners (Dewaele and Li 2020;Gkonou 2013;Horwitz, Horwitz, and Cope 1986). This is because the language classroom seems to be conducive to language anxiety as students can find themselves in inauthentic situations when they have to produce output in a language they have not mastered yet, speak publicly in that language and be subject to negative evaluations from their teachers or peers (Gkonou 2013;Liu and Xiangming 2019;Price 1991). In fact, speaking in a foreign language has been considered as one of the most face-threatening experiences for language learners (Dörnyei 2001;Gkonou 2011;Young 1999).…”
Section: Introductionmentioning
confidence: 99%